(untitled) - Futrell, Charles (Boston, 1998)
In this text the author draws on his own experience as a sales professional rather than from a theoretical perspective. He continues to develop contemporary themes such as relationship selling and technology around his classic approach.
Keywords: Selling,Bán hàng